An overview of Mobile Telecom Industry of Bangladesh: an important partner of Government from many aspects, case study on Grameenphone the largest telecom service provider in Bangladesh - Chowdhury, Ziaul Ahsan (BRAC University, 2014)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2013.